HLA Mismatching Strategies for Solid Organ Transplantation – A Balancing Act - Zachary, Andrea A.; Leffell, Mary S. (Frontiers in Immunology, 2016)
HLA matching provides numerous benefits in organ transplantation including better graft function, fewer rejection episodes, longer graft survival, and the possibility of reduced immunosuppression. Mismatches are attended by more frequent rejection episodes that require increased immunosuppression that, in turn, can increase the risk of infection and malignancy. HLA mismatches also incur the risk of sensitization, which can reduce the opportunity and increase waiting time for a subsequent transplant. However, other factors such as donor age, donor type, and immunosuppression protocol, can affect the benefit derived from matching. Further, finding a well matched donor may not be possible for all patients and usually prolongs waiting time. Strategies to optimize transplantation for patients without a well matched donor should take into account the immunologic barrier represented by different mismatches: what are the least immunogenic mismatches considering the patient’s HLA phenotype; should repeated mismatches be avoided; is the patient sensitized to HLA and, if so, what are the strengths of the patient’s antibodies? This information can then be used to define the HLA type of an immunologically optimal donor and the probability of such a donor occurring. A probability that is considered to be too low, may require expanding the donor population through paired donation or modifying what is acceptable which may require employing treatment to overcome immunologic barriers such as increased immunosuppression or desensitization. Thus, transplantation must strike a balance between the risk associated with waiting for the optimal donor and the risk associated with a less than optimal donor.